Error Analysis on the Use of Future Tense in Students' Writing Assignment - Rohmiyati, Yuli; Fatoni, Ana Utami (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2024)
Writing is the most difficult and complex skill for second language learners compared to other skills. Students need to practice and learn how to write. You can use error analysis to determine how well learners are learning a language. This study aims to identify the types of errors in the use of the future tense on students' writing assignments by the third semester of students Statistic Study Program 2022-2023 at Universitas Bina Bangsa Serang - Banten. This study observed 11 students and used a qualitative descriptive method. This research found that the students made three different types of errors based on Ellis' theory. The most frequent errors that students made were omission errors (24 data or 51%. The following were misformation errors (19 data or 42%) and the lowest were misordering errors (3 data or 7%). The errors that the students make can be used as feedback by the lecturer to implement remedial teaching activities, give the students extra exercises, and use various strategies that are suitable for the students.